EPICS: Efficient Parallel Pattern Fault Simulation for Sequential Circuits via Strongly Connected Components - Wang, Mingjun; Wang, Hui; Mu, Jianan; Zhang, Xinyu; Sun, Bin; Wen, Yihan; Liu, Zizhen; Gu, Feng; Gao, Jun; Liang, Shengwen; Ye, Jing; Li, Xiaowei; et al. (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
As functional safety of electronic chips gains importance in autonomous vehicles and aerospace, standards like ISO 26262 mandate high diagnostic coverage, requiring extensive gate-level fault simulations. However, for large-scale industrial sequential circuits, these simulations are time-consuming, creating a significant bottleneck in chip development. Prior approaches have focused on reducing computational complexity and optimizing CPU hardware usage by minimizing redundant computations during fault propagation and leveraging bit-level parallel processing capabilities. Techniques like parallel-pattern and event-driven simulations have improved performance in combinational circuits but face limitations in sequential circuits due to timing dependencies within loops. The challenge lies in parallelizing simulations across different cycles without violating these dependencies, which is exacerbated by the complex feedback structures in SCCs. In this work, we propose a novel parallel-pattern fault simulation framework that combines loop fusion with efficient event traversal to accelerate sequential circuit simulations. By compiling simple loops into larger nodes, we reduce the number of feedback events without introducing excessive redundancy. For larger SCCs, we develop specialized algorithms for selecting loop entrance nodes based on indegree analysis and implement the lazy propagation strategy for internal nodes. This approach minimizes simulation events caused by inaccurate predictions and reduces overhead associated with false event propagation. We integrate these techniques into our simulation framework, EPICS, which strategically mixes compiled and event-driven simulations to optimize performance. Experimental results demonstrate that EPICS achieves a 5.94 × speedup over state-of-the-art commercial tool while maintaining the same fault coverage.